Network-sensitive financial regulation - Enriques, L; Romano, A; Wetzer, T (University of Iowa, 2020)
Shocks that hit part of the financial system, such as the subprime mortgage market in 2007, can propagate through a complex network of interconnections among financial and non-fmancial institutions. As the financial crisis of 2007-2009 has shown, the consequences for the entire economy of such systemic risk materializing can be catastrophic. Following the crisis, economists and policymakers have become increasingly aware that the structure of the financial system is a key determinant of systemic risk. A wide consensus now exists among them that network theory is the natural framework for studying systemic risk. Yet, most of the existing rules in financial regulation are still "atomistic, " in that they fail to incorporate the fact that each individual institution is part of a wider network. This Article shows that policies building upon insights from network theory (network-sensitive policies) can address systemic risk more effectively than traditional atomistic policies, also in areas where an atomistic approach would seem natural, such as the corporate governance of systemically important financial institutions. In particular, we consider four prescriptions for the governance of systemically important institutions (one on directors' liability, two on executive compensation and one on failing financial institutions' shareholders appraisal rights in mergers) and show how making them network-sensitive would both increase their effectiveness in taming systemic risk and better calibrate their impact on individual institutions.